STRATA: The Research Process in the Making of a Performance-Based Film - Pagnes, Andrea; Stenke, Verena; Quin, Douglas; disley, daz (Performance Matters, 2023)
Does a performance-based film as a creative artifact contribute new knowledge on the topics it adresses partly through its practice and outcomes? The focus of this article is on the performance-based film project STRATA. Under the direction of artist duo Verena Stenke and Andrea Pagnes (VestAndPage), STRATA brings together artists, performers, scholars, and researchers from the humanities and social sciences through collaborations and interdisciplinary processes. Locations featured in the film include the Swabian Jura caves in Germany, which were used for shelter by Ice Age humans forty thousand years ago. VestAndPage intend to open up a contemporary discourse on the past by engaging performing artists as they confront the concept of deep time and layers of memory in human history. They investigate the human body as a site that exists in continuity with the geological, rather than cut away from it, undertaking site-specific/site-responsive performances within caves and grottos. Working from the a priori assumption that everything in the world is interconnected and coexists with its environment, they take ecological thinking as an entry point to enliven an emerging corporeal epistemology to inform a more holistic and multicultural perspective. In the article, the authors attempt to trace continuities between their research activity on performance, filmmaking, sound and light design practices, and the methodological differences between practice-based research in moving images and academic research in film and image studies. They recount the evolution of their thinking, sensations experienced, practice-based artistic research, and working methods, which draw largely upon phenomenology and heuristic processes.